Wetting phenomena in films of molecular hydrogen isotopes - Albrecht, U.; Conradt, R.; Herminghaus, S.; Leiderer, P. (Физика низких температур, 1996)
We have investigated various aspects of the wetting behavior of hydrogen films (including the heavier isotopes) using surface plasmon resonance, light scattering, and photoelectron emission. Studies in the vicinity of the triple point (T₃(H₂) = 13,96 K) confirmed the known «triple point wetting», and gave no indications for a prewetting transition in this range. At low temperatures (7 < T₃/3) the equilibrium film thickness reaches only a few monolayers. Thicker films, prepared by quench-condensation of H₂ gas at 1.5 K, undergo a dewetting process during annealing: most of the film material contracts to clusters, and in between the films thins down to its equilibrium thickness. This surface diffusion process is thermally activated, with an activation energy of 23 К (in the case of H₂). The dewetting kinetics has not revealed any indication for a surface-molten layer on the solid films at low temperatures, or for a superfluid component.